2012
DOI: 10.1073/pnas.1200781109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of chemoreceptor arrays revealed by cryoelectron tomography of Escherichia coli minicells

Abstract: The chemoreceptors of Escherichia coli localize to the cell poles and form a highly ordered array in concert with the CheA kinase and the CheW coupling factor. However, a high-resolution structure of the array has been lacking, and the molecular basis of array assembly has thus remained elusive. Here, we use cryoelectron tomography of flagellated E. coli minicells to derive a 3D map of the intact array. Docking of high-resolution structures into the 3D map provides a model of the core signaling complex, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
339
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(369 citation statements)
references
References 66 publications
18
339
2
Order By: Relevance
“…1B), each CheA protomer contacts only one of the three dimers in the trimer of receptor dimers, and each CheW contacts a single, different dimer ( Fig. 1 C and D) (9,10). This suggested that only the dimer in direct physical contact with CheA P5 or alternatively only the dimer in direct contact with CheW had the ability to inhibit the kinase activity of the trimer-associated CheA protomer.…”
Section: Preparation Of Nanodiscs With Mixed Chemoreceptor Compositionsmentioning
confidence: 97%
See 2 more Smart Citations
“…1B), each CheA protomer contacts only one of the three dimers in the trimer of receptor dimers, and each CheW contacts a single, different dimer ( Fig. 1 C and D) (9,10). This suggested that only the dimer in direct physical contact with CheA P5 or alternatively only the dimer in direct contact with CheW had the ability to inhibit the kinase activity of the trimer-associated CheA protomer.…”
Section: Preparation Of Nanodiscs With Mixed Chemoreceptor Compositionsmentioning
confidence: 97%
“…Instead, we considered a model based on structure of the core complex that was determined experimentally by a combination of electron tomography and X-ray crystallography (9,10). In that structure, among the dimers in the receptor trimers of dimers there are dimer-specific contacts with CheA and with CheW.…”
Section: Preparation Of Nanodiscs With Mixed Chemoreceptor Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemosensory proteins are found universally in large macromolecular clusters known as "chemotactic signaling arrays" (2)(3)(4)(5). MCPs, together with CheA and CheW, form the sensory core of these clusters.…”
mentioning
confidence: 99%
“…As a result, species that generate thin cells, such as Rhodobacter sphaeroides and C. crescentus, make it possible to visualize protein complexes if they are sufficiently concentrated. E. coli and other larger rod-shaped cells are difficult to image because they are too thick, although tiny minicells of E. coli and other species have recently been exploited to visualize surface protein assemblies [88][89][90].…”
Section: Viewing Native Divisome Structures By Cryo-electron Tomographymentioning
confidence: 99%